PENGUJIAN ARBITRAGE PRICING THEORY (APT) SEBAGAI PREDICTOR PENGEMBALIAN SAHAM YANG DIHARAPKAN ( STUDI KASUS PADA INDUSTRI PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Rundengan, Fanda Daisy Prully; Parengkuan, Tommy; Saerang, Ivonne (Universitas Sam Ratulangi, 2013)
The impact of the economic crisis caused investors have difficulty in analyzing and predicting stock returns of the company. No exception to the banking industry shares are listed on the Indonesia Stock Exchange (BEI). In predicting stock returns are expected, there are two models that are often used by investors, the capital asset pricing model (CAPM) and the arbitrage pricing theory (APT). APT basically use reasoning stating that two investment opportunities that have the same characteristics identical bias not sold with different prices. The concept used is hokum one price (the law of one price). Analysis used in the study is the analysis of two different test average. Where comparing ten banking industry Stock Exchange Securities registered Indonesian (IDX). After conducting a hypothesis test using the SPSS output in the form of test results obtained bedadua average dependent samples, bahwathitung for APT testing by comparing the actual return (Ri) and expected return (ERI) stock with a variance equal to propabilitas assumet is 0.290 0,1.620. Therefore, P-value 0.290> 0.05, results showed that the expected return is not berbedas ignifikan with actual return (significant 0.290) This means that the hypothesis stated:.